DISTRACT study: evaluating kaleidoscope distraction as part of multimodal pain management in paediatric dressing changes – study protocol of a single centre randomised trial - Andreas Wladis; Cornelis J H M van Laarhoven; Ravi Naidoo; Frederike J C Haverkamp; Måns Muhrbeck; Laura Pompermaier; Edward C T H Tan (BMJ Open)
Introduction Procedure-related pain should be minimised to prevent psychological trauma and the potential negative consequences on body physiology. Dressing changes in paediatric patients with burn injuries are frequently performed with analgesics alone where sedation is not indicated, especially in minor and superficial burns. It is hypothesised that distraction methods can be used in addition to pain alleviating medication to reduce the experience of pain in these patients.Objective With this research project, we aim to assess the effectiveness of a simple, inexpensive, non-electronic distraction method, a kaleidoscope, to reduce acute pain experienced in paediatric patients undergoing dressing changes in the outpatient clinic.Methods and analysis A randomised controlled trial will be performed at the Ngwelezana Tertiary Hospital, Empangeni, South Africa. Paediatric patients between the ages of 5 years and 12 years with minor and superficial partial thickness burn injuries who require dressing changes in the outpatient clinic, without sedation, will be randomised into two groups with a 1:1 allocation ratio. Fixed randomisation will be performed by a computer random number generator. The control group will receive standard practice of care which concerns a dressing change without any distraction methods, and the intervention group will receive distraction by use of a kaleidoscope as an additional method for potential pain alleviation. Patients in both groups will receive paracetamol or non-steroidal anti-inflammatory drugs when indicated according to hospital protocol. The primary outcome will be the change in pain score from pre-procedural to pain score during the dressing change and will be analysed with a linear regression analysis. Additionally, subanalyses will be performed to evaluate potentially modifying factors on the treatment effect. This will also be evaluated with a linear regression analysis and correlated with caregiver and healthcare worker observational pain scores. Participants and assessors are not blinded to group assignment due to the nature of the intervention. To achieve a power of 80% and a level of significance of 5% for detecting at least a 1-point difference in change in pain scores between the intervention and control group, a sample size of 50 patients in each group is required.Ethics and dissemination This study evaluates a non-invasive adjunct to reduce pain in children who undergo a painful procedure. Ethical approval has been granted from the University of Kwazulu-Natal’s biomedical research and ethics committee and the ethics and research committee of Ngwelezana Tertiary Hospital prior to recruitment (ref no. BREC/00005194/2023). Written informed consent will be acquired from all study participants’ caregivers. Study findings will be presented orally to staff at the paediatric burn unit of Ngwelezana Tertiary Hospital (study location). The research methodology and results will be presented at scientific conferences and will be submitted for publication in a peer-reviewed journal.Trial registration number NCT06591195.